IMPACT OF AIS AND STRESSED OUT AN EMPLOYEES TO THEIR PERFORMANCE AT PT EFRATA RETAILINDO - Retno Sari, Wiwit Ayu; Suhendro, Suhendro; Dewi, R. Riana (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
This research aims to test the influence of accounting information system and work stress on performance of employees of PT Efrata Retailindo. The type of research used in this research is quantitative research. The source of the data in the research is primary data. The population in this study are all employees of PT Efrata Retailindo totalling 47 people. Sampling techniques in the study using a purposive sample. While the data collection method used is to use the questionnaire to all employees of PT Efrata Retailindo. Data analysis techniques using multiple linear regression analysis. Based on the results of the study it can be concluded that work stress had no effect on performance of employees of PT Efrata Retailindo, while information systems accounting effect on the performance of the employees of PT Efrata Retailindo. The value of the coefficient of determination (R2) amounting to 0.106. This indicates that variansi on a variable performance practice undertaken by the company PT Efrata Retailindo of 10.6% can be explained by work stress variables and accounting information systems, while the remaining 89.4% explained by other factors outside the researched.